2021
DOI: 10.2174/1567205018666210823095044
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Granule Proteins Inhibit Amyloid Beta Aggregation and Neurotoxicity

Abstract: Background: A role for neutrophils in the pathogenesis of Alzheimer’s disease (AD) is emerging. We previously showed that the neutrophil granule proteins cationic antimicrobial protein of 37 kDa (CAP37), cathepsin G (CG), and neutrophil elastase (NE) directly bind the amyloid-beta peptide Aβ1-42, a central player in AD pathogenesis. CAP37, CG, and NE are serine proteases that can cleave Aβ1-42 at different sites and with different catalytic activities. Objective: In this study, we compared the effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…AD patients also had a greater proportion of cells expressing CCR4 (expressed on Th2 cells) and CCR5 (Th1 cells and dendritic cells). Kasus-Jacobi et al [ 39 ] used mass spectrometry and in vitro aggregation methods to detect the activity of neutrophil elastase (NE) and cathepsin G (CG) against amyloid-beta peptide A β 1-42 and found that the peptide derived from CAP37 mimics the quenching and inhibitory aggregation effects of A β 1-42 full-length protein. In addition, the peptide inhibited the neurotoxicity of the most toxic A β 1-42 aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…AD patients also had a greater proportion of cells expressing CCR4 (expressed on Th2 cells) and CCR5 (Th1 cells and dendritic cells). Kasus-Jacobi et al [ 39 ] used mass spectrometry and in vitro aggregation methods to detect the activity of neutrophil elastase (NE) and cathepsin G (CG) against amyloid-beta peptide A β 1-42 and found that the peptide derived from CAP37 mimics the quenching and inhibitory aggregation effects of A β 1-42 full-length protein. In addition, the peptide inhibited the neurotoxicity of the most toxic A β 1-42 aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that these neutrophil proteins: cathepsin G (CG), neutrophil elastase (NE), and cationic antimicrobial protein of 37 kDa (CAP37) could modulate neurotoxicity in AD by influencing the Aβ-RAGE interaction [ 2 ]. In a follow up study, we found that NE and CG could cleave Aβ 1–42 , and inhibit its aggregation into oligomers and fibrils [ 16 ]. In contrast, CAP37 did not efficiently cleave Aβ 1–42 , but inhibited Aβ 1–42 oligomerization and fibrillation, most likely through direct binding to the unaggregated form [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a follow up study, we found that NE and CG could cleave Aβ 1–42 , and inhibit its aggregation into oligomers and fibrils [ 16 ]. In contrast, CAP37 did not efficiently cleave Aβ 1–42 , but inhibited Aβ 1–42 oligomerization and fibrillation, most likely through direct binding to the unaggregated form [ 16 ]. Of the three proteins, CG was found to be the most potent to inhibit the neurotoxicity of Aβ 1–42 , in a cultured neuron cell line [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations